Making up and renovation of trains - Vaičiūnas, Gediminas; Lingaitis, Leonas P. (Transport, 2002)
Major constituent parts of the railway system are rolling stock and various objects making its infrastructure. Their maintenance is rather expensive, while renovation requires large investments. The researchers all over the world are working hard to make these investments effective. To make a decision in economics its economic effect should be established first. Generally, the latter is expressed as the repay time of investment or the economic effect in the particular period of time specified according to the particular technical requirements. The repay time is usually calculated optimizing the choice of the particular elements (i.e. an.engine, gear-box, transmission, etc.) of the train. The optimization of the selection of the trains would require a comparative analysis of economic effects (expressed in monetary units at the particular time interval) of the alternative solutions available. If the target objects of the investments are well-known, the first approach described in the present paper may be used to determine the repay time of investment thus enabling us to check the effectiveness of a potential investment. If an object for the potential investment should be determined, implying that its major characteristics should be described, the second method based on increasing the economic effect may be applied. First Published Online: 19 Dec 2011